The fate of coastal habitats in the Venice Lagoon from the sea level rise perspective. (September 2018) - Ivajnšič, Danijel; Kaligarič, Mitja; Fantinato, Edy; Del Vecchio, Silvia; Buffa, Gabriella
Abstract: Coastal wetlands worldwide are retreating owing to several anthropogenic pressures and accelerated sea level rise (SLR). The importance of preserving salt marshes and the services they provide is being increasingly recognized and wetlands have become the target of several international initiatives and conservation regulations. Thus, geospatial models with applicable high spatial resolution results estimating the potential development of wetland habitats under climate change are urgently needed in order to prepare proper conservation measures and management strategies in an opportune moment. This study aimed at predicting the potential impact of SLR on salt marsh habitats in the Venice Lagoon. Habitat turnover over time was modelled based on a fine-scale vegetation map, relative elevation measurements, and most relevant environmental data (subsidence and accretion) connected with SLR. Three model-based SLR scenarios (GFDL P50, RCP4.5, RCP8.5) and the local linear trend were considered. Clear differences between the northern and southern parts of the lagoon emerged. By 2075, 37 to 48% (model-based scenarios) or even 51% (linear scenario) of the Venice lagoon coastal habitats could lie under water. Although nearly all habitats evidenced a decrease in their extent by 2050 and beyond, our results also suggest that different types of marshes will respond differently to SLR. Exactly this information (what, where and when) is of crucial importance for decision makers to initiate enhance planning and management policies. Moreover, the forecasted changes in tidal marsh area and the presented cost effective methodological approach is transferable to other temperate areas faced with comparable SLR rates. Highlights: Sea level rise will reshape Venice Lagoon's coastal habitats. Salt marsh vegetation could disappear under GFDL P50 or RCP8.5 climate scenarios. Differences in habitat dynamics between the N and S parts of the lagoon are evident. The methodological approach is applicable in other temperate tidal marshes under SLR. Geospatial results serve for strategic spatial planning and policy management.